Evaluation of four pasture legumes species as forages and cover crops in oil palm plantation - Rijanto Hutasoit; Juniar Sirait; Andi Tarigan; D. H. Ratih (Indonesian Center for Animal Research and Development (ICARD), 2017)
Pasture legumes is a very high quality of forage. The limited land is the problem of its development. Integration with oil palm plantations is one of the potentials for its development. This study was aimed to investigate the productivity of several legumes (Arachis glabrata, Stylosanthes guianensis, Clitoria ternatea, and Chamaecrista rotundifolia) as forages and cover crop. The potential tests were conducted in oil palm area of 4608 m2, in a complete block design with four treatments (legume species) and three replications. Parameters observed were: Legum production, leaf/stem ratio, chemical composition of legume, concentration of N, P in the soil, microbes in the soil, leguminous digestibility and palm fruit production. Results showed that the highest legume production (DM) was (P<0.05) in the species of Clitoria ternatea (16.15 tons ha-1year-1), the highest leaf/stem ratio (P<0.05) was in the Arachis glabrata (2.09). The chemical composition (DM) did not differ (P>0.05) ranged from 33.75 to 35.75%, the organic matter (OM) varied greatly (P<0.05) the highets was in Clitoria ternatea. The highest Crude protein (P<0.05) was in Clitoria ternatea 17.84%. NDF concentrations did not differ (P>0.05). The lowest ADF concentration (P<0.05) was in Chamaecrista rotundifolia. The concentration of N in the soil indicated that early year of activity was similar (average 0.10%), at the end of activity increased (P<0.05) in treatment Stylosanthes guianensis (0.16%). The highest population of N-fixation bacteria of 1.76x109 and phosphate solvent of 9.8x105 were in the treatment of Clitoria ternatea. Production of fresh fruit bunches of the palm was relatively similar (P>0.05) ranged from 16.52-19.21 tons ha-1year-1. It is concluded that Clitoria ternatea is the best species of legume tested as forage and cover crop in oil palm plantations.